Implementation of Microfluidics for Antimicrobial Susceptibility Assays: Issues and Optimization Requirements - Parsley, Nicole C.; Smythers, Amanda L.; Hicks, Leslie M. (Frontiers in Cellular and Infection Microbiology, 2020)
Despite the continuous emergence of multi-drug resistant pathogens, the number of new antimicrobials reaching the market is critically low. Natural product peptides are a rich source of bioactive compounds, and advances in mass spectrometry have achieved unprecedented capabilities for the discovery and characterization of novel molecular species. However, traditional bioactivity assay formats hinder the discovery and biochemical characterization of natural product antimicrobial peptides (AMPs), necessitating large sample quantities and significant optimization of experimental parameters to achieve accurate/consistent activity measurements. Microfluidic devices offer a promising alternative to bulk assay systems. Herein, a microfluidics-based bioassay is compared to the traditional 96-well plate format in respective commercially-available hardware. Bioactivity in each assay type is compared using a Viola inconspicua peptide library screened against E. coli ATCC 25922. Brightfield microcopy is used to determine bioactivity in microfluidic channels while both common optical and fluorescence-based measurements of cell viability are critically assessed in plate-based assays. Exhibiting some variation in optical density and fluorescence-based measurements, all plate-based assays conferred bioactivity in late eluting V. inconspicua library fractions. However, significant differences in the bioactivity profiles of plate-based and microfluidic assays are described, and may be derived from the materials comprising each assay device or the growth/assay conditions utilized in each format. While new technologies are necessary to overcome the limitations of traditional bioactivity assays, we demonstrate that off-the-shelf implementation of microfluidic devices is non-trivial and significant method development/optimization is required before conventional use can be realized for sensitive and rapid detection of AMPs in natural product matrices.